Clinical biochemistry of domestic animals - Kaneko, Jiro J.; Harvey, John W.; Bruss, Michael (Academic Press, 1997)
This updated and expanded Fifth Edition of Clinical Biochemistry of Domestic Animals brings together in a single comprehensive volume all the pertinent information regarding the biochemistry of disease and non-disease states in animals. Clinical veterinarians and animal scientists now routinely use many of the same diagnostic and therapeutic tools used to identify and treat diseases and metabolic disorders in humans, making this book an indispensable teaching, learning, and application resource for anyone engaged in the care, health, and welfare of animals. This book concentrates on the various rationales and interpretations regarding the biochemistry of disease in animals. It includes newly updated chapters with current references and new chapters on clinical toxicology and avian clinical biochemistry. Key Features * Brings together in a single comprehensive volume all the pertinent information regarding the biochemistry of disease and non-disease states in animals * Includes newly updated chapters with current references * Contains new chapters on clinical toxicology and avian clinical biochemistry * Concentrates on the various rationales and interpretations regarding the biochemistry of disease in animals.